Glass-transition behaviour of plasticized starch biopolymer system - A modified Gordon-Taylor approach - Chaudhary, Deeptangshu; Adhikari, B.; Kasapis, S. (Elsevier BV, 2011)
Two plasticizers namely, glycerol and xylitol, based on their similar molecular size (6.3 A) but different molecular weights (Glycerol-92; Xylitol-152) were selected for studying the glass-transition behaviour (rubber like behaviour) in multi-plasticized starch biopolymer with about 70% amylopectin structure. In the calorimetry measurements, glass-transition temperatures (onset temperature for bulk viscous flow) of plasticized samples were higher than non-plasticized samples at low water activities, thus showing typical antiplasticization behaviour. However, when plasticizer concentration was increased up to 15% and 20% wt, all plasticized samples showed significant reduction in glass-transition temperature. We used a modified Gordon-Taylor model to understand the competitive plasticization of glycerol and xylitol in presence of water, and suggest that competitive plasticization exists and occurs at a threshold amount of matrix free water content, due to strong three-way interactions: starch-plasticizer, plasticizer-plasticizer/water and starch-water. This competitive interaction is significant in determining the onset temperature for viscous flow behaviour; at higher matrix water content, the Gordon-Taylor constant was relatively unaffected by the plasticizer amount, and water was the dominant plasticizer. A new interaction parameter that separates the starch-plasticizer interaction in a starch-plasticizer-water system is also discussed.